A Metacognitive Model of the Effects of Susceptibility to Persuasion Self-Beliefs on Advertising Effects. Issue 4 (2nd October 2017) - Chang, Chingching
Abstract : This study postulates that people's beliefs about their own susceptibility to persuasion efforts can influence advertising effects. It thus represents the first explication of the process by which self-beliefs determine advertising effects, through their influence on the subjective experience of the ease of being persuaded. Integrating three research streams (metacognition, persuasion knowledge, and cognitive correction), the current study proposes a model of three influence patterns, which are contingent on whether people perceive the advertising message to be high in manipulative intent and whether people are motivated to be accurate in their judgments. If advertising messages are low in manipulative intent, such that the persuasion seems acceptable, susceptibility self-beliefs influence people's attitudes toward the advertised products or issues (i.e., expected effects). If advertising messages are high in manipulative intent, such that persuasion seems unacceptable, people exhibit suppression (no effects) if they have weak accuracy motives, but they exhibit overcorrection (opposite effects) if they are strongly motivated to be accurate. Five studies test these predictions and reveal some demographic characteristics associated with self-beliefs about susceptibility to persuasion. The findings thus have important implications for advertising practitioners.